Association between adverse oral conditions and cognitive impairment: A literature review - Wei, Tianhao; Du, Yifeng; Hou, Tingting; Zhai, Chunjuan; Li, Yuqi; Xiao, Wei; Liu, Keke (Frontiers in Public Health, 2023)
Oral environment deterioration results from a lack of self-cleaning ability in patients with cognitive dysfunction, but it is also a risk factor for cognitive dysfunction. Oral problems can be alleviated and improved through self-management and medical examination. In this review, we demonstrate that timely and effective oral intervention in high-risk groups can play an important role in delaying cognitive impairment and dementia. We also discuss the relationship between poor oral status and cognitive dysfunction from the perspective of epidemiology, aiming to explain emphasize the importance of oral health for cognition and provide scientific evidence for further research on this relationship.